2010
DOI: 10.1097/aog.0b013e3181e408f2
|View full text |Cite
|
Sign up to set email alerts
|

Oral Misoprostol and Vaginal Isosorbide Mononitrate for Labor Induction

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…Nitric oxide donors like isosorbide mononitrate have been used as cervical ripening agents in first trimester and for induction of labour at term in the past. [4][5][6] Nitric oxide donors induce production of matrix metalloproteinases namely MMP-1 and MMP-9, which are essential for collagen degradation. 7 It also increases proinflammatory cytokines and prostaglandins.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide donors like isosorbide mononitrate have been used as cervical ripening agents in first trimester and for induction of labour at term in the past. [4][5][6] Nitric oxide donors induce production of matrix metalloproteinases namely MMP-1 and MMP-9, which are essential for collagen degradation. 7 It also increases proinflammatory cytokines and prostaglandins.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, several studies have tried to show the effect of NO on cervical pre-induction ripening. [ 15 16 17 18 19 20 21 22 ] Many of these studies have used isosorbide mononitrate and no study has been conducted with ISDN so far. Findings of previous studies indicated that delivery length from the onset of intervention in the misoprostol group was shorter and the need for induction in this group was lower.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of previous studies indicated that delivery length from the onset of intervention in the misoprostol group was shorter and the need for induction in this group was lower. [ 16 ] Due to difficult access to misoprostol and its high cost in Iran, and dangers of using misoprostol including systolic tachycardia, uterine hyperstimulation, and other risks to the fetus, this medication should always be prescribed in certain circumstances only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now data about the use of ΝΟ donors in induction of labor [8,9] and also first trimester terminations of pregnancy [2,10]. The published results are contradictory and inconclusive.…”
Section: Introductionmentioning
confidence: 97%